2015
DOI: 10.1007/s10903-015-0164-6
|View full text |Cite|
|
Sign up to set email alerts
|

Korean American Women and Mammogram Uptake

Abstract: A high percentage of Korean American (KA) women have never had a mammogram, which puts them at greater risk for late-stage breast cancer. The aim of this study was to compare health beliefs and spousal support about breast cancer and screening between KA women with and without a history of mammogram completion. Crosssectional data were obtained from 428 non-adherent married KA women. KA women who never had a mammogram were younger, had less access to health care, had less knowledge, and had lower perceived sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 39 publications
5
42
1
1
Order By: Relevance
“…The positive influence of marital status on BCS is well articulated in the literature. Our findings of superior BA participation, as well as CBE and mammogram attendance among married and de facto women, mirror those reported for migrants in Denmark 19 and the US 18,20 . A possible explanation may lie in the important role of a spouse in mediating attitudes towards BCS 31 .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The positive influence of marital status on BCS is well articulated in the literature. Our findings of superior BA participation, as well as CBE and mammogram attendance among married and de facto women, mirror those reported for migrants in Denmark 19 and the US 18,20 . A possible explanation may lie in the important role of a spouse in mediating attitudes towards BCS 31 .…”
Section: Discussionsupporting
confidence: 80%
“…14,15 Previous studies have identified sociodemographic differences associated with BCS participation among immigrant women in Western countries. [15][16][17][18] Compliance with screening recommendations has been reported to vary by marital status, education level, employment status and age, as well as acculturation level. Married and de facto Arab 13,16 and Vietnamese 15 women have consistently reported higher mammographic screening rates compared to their unmarried counterparts.…”
Section: Prevalence and Sociodemographic Correlates Of Routine Breastmentioning
confidence: 99%
See 2 more Smart Citations
“…for the whole instrument was .85, and that for the 3 subscales ranged from .81 to .93. 36 The instrument is composed of 3 subscales: (1) attitudes toward general health check-ups containing 4 items, which explored whether the participants normally presented themselves for general medical check-ups in the absence of signs or symptoms of illness; (2) knowledge and perceptions about breast cancer, also containing 4 items, which examined cultural beliefs about breast cancer; and (3) barriers to mammographic screening practices with 5 items covering personal and practical issues perceived by a participant as discouraging her from presenting for mammographic screening. Participants were required to make ratings for each item along a 5-point Likert scale ranging from ''strongly agree'' (score of 1) to ''strongly disagree'' (score of 5).…”
Section: Instrumentmentioning
confidence: 99%